2002
DOI: 10.1038/sj.bjc.6600295
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids uptake and their effect on cell cycle of human colon adenocarcinoma cells (Caco2)

Abstract: Green tea, mainly through its constituents epigallocatechin gallate, epigallocatechin, epicatechin gallate and epicatechin, has demonstrated anticarcinogenic activity in several animal models, including those for skin, lung and gastro-intestinal tract cancer, although less is known about colorectal cancer. Quercetin, the major flavonoid present in vegetables and fruit, exerts potential anticarcinogenic effects in animal models and cell cultures, but less is known about quercetin glucosides. The objectives of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
79
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 42 publications
14
79
1
3
Order By: Relevance
“…They concluded that IQ is a promising antioxidant agent but that it did not inhibit Caco2 cellular growth [79] . In 2005, Kern et al [80] reported a perspective on the antiproliferative effect and demonstrated the potent EGFRinhibitory properties of polyphenolrich apple juice extract in adenocarcinoma colon in vitro model (HT29) [80] .…”
Section: Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that IQ is a promising antioxidant agent but that it did not inhibit Caco2 cellular growth [79] . In 2005, Kern et al [80] reported a perspective on the antiproliferative effect and demonstrated the potent EGFRinhibitory properties of polyphenolrich apple juice extract in adenocarcinoma colon in vitro model (HT29) [80] .…”
Section: Colon Cancermentioning
confidence: 99%
“…In 2002, Salucci et al [79] suggested that the antioxidant activity of flavonoids was not involved in their inhibition of the growth of colon adenocarcinoma cells (Caco2). They concluded that IQ is a promising antioxidant agent but that it did not inhibit Caco2 cellular growth [79] .…”
Section: Colon Cancermentioning
confidence: 99%
“…Therefore, the cytotoxic effect of algae, via the inhibition of the proliferation of Caco2 cells is likely to be related to their content of these compounds especially polyphenolics and flavonoids [39]. For example, quercetin shows antioxidant activity that is believed to have a cytoprotective role against oxidative stress [40].…”
Section: Cytotoxic Activity Of Crude Algae Extractsmentioning
confidence: 99%
“…Quercetin, a major bioflavonoid in human diet, has been identified as a chemotherapeutic agent for the treatment of breast cancer (Singhal et al, 1995;Choi et al, 2001), colon cancer (Salucci et al, 2002), ovarian cancer (Chan et al, 2003) and prostate cancer (Knowles et al, 2000;Nakanoma et al, 2001;Kobayashi et al, 2002). Antiproliferative action of quercetin is hypothesised to be mediated by attenuating phosphorylation of activated hsp transcription factor (hsf), shortly after its trimerisation (Nagai et al, 1995;Lee et al, 1998), thereby resulting in increased susceptibility of hsf to proteolytic degradation and as a consequence inhibiting all downstream events, including hsp expression (Li et al, 1999).…”
mentioning
confidence: 99%